2019
DOI: 10.1002/tesq.506
|View full text |Cite
|
Sign up to set email alerts
|

Emergent Leadership and Group Interaction in the Task‐Based Language Classroom

Abstract: Learning language in the classroom often means interacting with peers in small groups. There is a growing body of empirical research highlighting the factors that have an impact on student interaction and an increasing focus on the social context. This article aims to broaden the focus of research by considering the influence of emergent leadership on group interaction and opportunities for language learning. Japanese university students in an oral English course were placed into random small groups, fixed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…In addition, the leadership emergence literature has unfolded across seven decades with research appearing in academic journals across multiple disciplines including (but not limited to): communication (Jiang et al, 2015), criminal justice (Bishopp, 2013), economics (Grunau & Pecoraro, 2017), education (Leeming, 2019), healthcare (Asiamah & Mensah, 2019), management (Hu et al, 2019), and psychology (Schaumberg & Flynn, 2012). Although it is clear that leader emergence research is multidisciplinary in nature, it is far from interdisciplinary—with many research endeavors published in management and applied psychology outlets ignoring highly relevant studies published in other disciplines.…”
mentioning
confidence: 99%
“…In addition, the leadership emergence literature has unfolded across seven decades with research appearing in academic journals across multiple disciplines including (but not limited to): communication (Jiang et al, 2015), criminal justice (Bishopp, 2013), economics (Grunau & Pecoraro, 2017), education (Leeming, 2019), healthcare (Asiamah & Mensah, 2019), management (Hu et al, 2019), and psychology (Schaumberg & Flynn, 2012). Although it is clear that leader emergence research is multidisciplinary in nature, it is far from interdisciplinary—with many research endeavors published in management and applied psychology outlets ignoring highly relevant studies published in other disciplines.…”
mentioning
confidence: 99%
“…With the exception of Leeming (2019), who showed that levels of emergent leadership predicted engagement with tasks, no studies in SLA have set out to focus on emergent leadership, although it has proven to be a factor in understanding interaction in several studies. Yashima, Ikeda, and Nakahira (2016) investigated silence in group discussions, and found that student leaders played a large role in determining the success of the interaction.…”
Section: Emergent Leadership In Groupsmentioning
confidence: 99%
“…Researchers have discussed and agreed on the importance of emergent leaders in groups (Dörnyei & Murphey, 2003;Ehrman & Dörnyei, 1998), and a limited body of empirical research has shown the impact that these leaders can have on the performance of the group (Leeming, 2019;Yashima et al, 2016;Tuan & Storch, 2007). However, the extent to which leadership influences task engagement is not understood, despite being of primary concern for language teachers.…”
Section: Group Membership and Engagementmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that successful collaboration during tasks depends, to an extent, on interpersonal dynamics (Leeming, 2019). Interpersonal dynamics focuses on the relationship between two people who may be part of a group, while group dynamics focuses on the processes that occur in groups (Ehrman and Dörnyei, 1998).…”
Section: Introductionmentioning
confidence: 99%